2016
DOI: 10.3892/or.2016.5197
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of filamin B splice variants in giant cell tumor cells

Abstract: Giant cell tumor of bone (GCT) is the most commonly reported non-malignant bone tumor in Hong Kong. This kind of tumor usually affects people aged 20–40 years. Also, it is well known for recurrence locally, especially when the tumor cannot be removed completely. Filamins are actin-binding proteins which contain three family members, filamin A, B and C. They are the products of three different genes, FLNA, FLNB and FLNC, which can generate various transcript variants in different cell types. In this study, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recently, FLNB has been considered one of the biomarkers for cancer. Splicing variants of FLNB expression have been reported to play key roles in the proliferation and differentiation of tumor cells (33). A recent study demonstrated that in HMLE cells (immortalized human mammary epithelial cells), FLNB interacts with forkhead box C1 (FOXC1) to form a complex (11).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, FLNB has been considered one of the biomarkers for cancer. Splicing variants of FLNB expression have been reported to play key roles in the proliferation and differentiation of tumor cells (33). A recent study demonstrated that in HMLE cells (immortalized human mammary epithelial cells), FLNB interacts with forkhead box C1 (FOXC1) to form a complex (11).…”
Section: Discussionmentioning
confidence: 99%
“…FLNB (Filamin B) is a cytoskeletal protein encoded by the gene on autosomal chromosome 3. It is cross-linked with actin to form a three-dimensional cytoskeletal network and maintain cell morphology (Tsui et al 2016;Devis et al 2017). FLNB is involved in many physiological and biochemical activities, including transcriptional regulation and cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…It has a key role in skeletal development and its pathogenic mutations are the solely cause of skeletal deformities (26). Recently, Tsui et al reported that differential expression of Filamin B splicing variants may play a key role in proliferation and differentiation of giant cell tumor of bone (27). Another intriguing study identified Filamin B in human sera as a potential biomarker for prostate cancer (28).…”
Section: Discussionmentioning
confidence: 99%